Early Diagnosis of Cutaneous Mucormycosis Due to Lichtheimia corymbifera After a Traffic Accident - Tyll, Tomas; Lyskova, Pavlina; Hubka, Vit; Muller, Martin; Zelenka, Lubomir; Curdova, Martina; Tuckova, Inna; Kolarik, Miroslav; Hamal, Petr (Mycopathologia, 2016)
A case report of cutaneous mucormycosis and obstacles to early diagnosis is presented. A 38-year-old male was involved in a car accident that led to amputation of both lower limbs. Subsequently, he developed fungal wound infection of the left lower limb stump. The infection was detected very early, although the diagnosis was difficult because only a small area was affected and histopathological examination was initially negative. The infection was proven by microscopy, culture and histopathology. The isolate was identified by sequencing of the rDNA ITS region gene (internal transcribed spacer region of ribosomal DNA) as Lichtheimia corymbifera. Liposomal amphotericin B and surgery were successful in management of the disease.
Keywords: Histocytochemistry; debridement; mužské pohlaví; histocytochemie; Male; výsledek terapie; rány a poranění; Humans; dopravní nehody; Amphotericin B; lidé; amfotericin B; mezerníky ribozomální DNA; DNA, Ribosomal Spacer; sekvenční analýza DNA; mukormykóza; Mucorales; Wounds and Injuries; Sequence Analysis, DNA; časná diagnóza; Treatment Outcome; Early Diagnosis; DNA, Fungal; Accidents, Traffic; Debridement; dospělí; Adult; Wound Infection; infekce v ráně; Mucormycosis; antifungální látky; DNA fungální; mikroskopie; Antifungal Agents; Microscopy